Macroeconomic dynamics under bounded rationality: On the impact of consumers' forecast heuristics - Tae-Seok Jang; Stephen Sacht (Kiel University, Department of Economics, 2018)
In this study, we analyze the macroeconomic dynamics under various shocks in two competing frameworks. Given the baseline New-Keynesian model, we compare the impulse response functions that stem from the hybrid version under rational expectations with the ones obtained in the forward-looking version under bounded rationality. For the latter, we assume heterogeneous agents who may adopt various forecast heuristics. We seek to understand which framework mimics real-world adjustments well and is therefore most suitable to describe economic adjustments over the business cycle.
Keywords: C53; D83; E12; E21; E32; 330; Bounded Rationality; Consumer Expectations; Forecast Heuristics; Impulse Response Functions; New-Keynesian Model